ACTIVITIES OF RULERS IN TEMURIYZADA IN LIBRARIES (Archive of Conferences, 2021)
A library, translated from Arabic into Persian, means a place where books are kept. Libraries are one of the few scientific institutions that have a collection of newspapers, magazines, books, video and audio recordings. The library is a cultural stronghold that provides regular access to printed and manuscript works, as well as the regular storage, collection and delivery of printed works to readers. This article describes the world-famous libraries built by the Timurids under their patronage.